Synthesis and Hydrolysis of Alkoxy(aminoalkyl)diorganylsilanes of the Formula Type R2(RO)Si(CH2)nNH2 (R = Alkyl, n = 1–3): A Systematic Experimental and Computational Study. Issue 11 (17th March 2016) - Ehbets, Julia; Lorenzen, Sabine; Mahler, Christoph; Bertermann, Rüdiger; Berkefeld, André; Poater, Jordi; Fritz‐Langhals, Elke; Weidner, Richard; Bickelhaupt, F. Matthias; Tacke, Reinhold
Abstract: Alkoxy(aminoalkyl)silanes are important precursors for the formation of amino‐functionalized polysiloxanes, which are used in many technical applications. To better understand the mechanism of the hydrolytic cleavage of the Si–alkoxy moiety of alkoxy(aminoalkyl)silanes (an important key step in the formation of amino‐functionalized polysiloxanes), a systematic experimental and computational study on the hydrolysis of alkoxy(aminoalkyl)diorganylsilanes of the formula type R2 (RO)Si(CH2 ) n NH2 (R = alkyl, n = 1–3) was conducted. For reasons of comparison, silanes of the formula types R2 (RO)SiC(H)MeCH2 NH2 and R2 (RO)Si(CH2 ) n X [R = alkyl; n = 1–3; X = N(H)Me, NMe2, piperidino, NMe3 + I –, N(H)COOMe, N(Me)COOMe] and compounds Me2 (MeO)Si(CH2 )6 Me and Me2 (MeO)Si(CH2 )6 NH2 were included in this study. For this purpose, the various silanes were synthesized and studied for their hydrolysis kinetics in CD3 CN/D2 O under acidic and basic conditions by using 1 H NMR spectroscopy as the analytic tool. These experimental investigations were complemented by computational studies (calculation of proton affinities, reaction barriers, and energies relative to reactants of intermediate transition complexes). The different hydrolysis reactivities observed are the result of a number of parameters, such as electronic and steric effects, the strong impact of the pD value, and intramolecular N–H··· O hydrogen bonds between the protonated amino group and the alkoxy leaving group. This comprehensive study provided deep insight into the mechanism of hydrolysis of analogous α‐, β‐, and γ‐amino‐functionalized alkoxy(aminoalkyl)diorganylsilanes of the formula type R2 (RO)Si(CH2 ) n NH2 (R = organyl, n = 1–3) and a series of related α/β/γ analogues with other nitrogen‐based functional groups. Abstract : Kinetic studies provided a deep insight into the mechanism of hydrolysis of analogous α‐, β‐, and γ‐amino‐functionalized alkoxy(aminoalkyl)diorganylsilanes of the formula type R2 (RO)Si(CH2 ) n NH2 (R = organyl, n = 1–3) and a series of related α/β/γ analogues with other nitrogen‐based functional groups.